Properties of Adenovirus Vectors with Increased Affinity to DSG2 and the Potential Benefits of Oncolytic Approaches and Gene Therapy - Nora A. Bahlmann; Raphael L. Tsoukas; Sebastian Erkens; Hongjie Wang; Franziska Jönsson; Malik Aydin; Ella A. Naumova; André Lieber; Anja Ehrhardt; Wenli Zhang (Viruses, 2022)
Carcinomas are characterized by a widespread upregulation of intercellular junctions that create a barrier to immune response and drug therapy. Desmoglein 2 (DSG2) represents such a junction protein and serves as one adenovirus receptor. Importantly, the interaction between human adenovirus type 3 (Ad3) and DSG2 leads to the shedding of the binding domain followed by a decrease in the junction protein expression and transient tight junction opening. Junction opener 4 (JO-4), a small recombinant protein derived from the Ad3 fiber knob, was previously developed with a higher affinity to DSG2. JO-4 protein has been proven to enhance the effects of antibody therapy and chemotherapy and is now considered for clinical trials. However, the effect of the JO4 mutation in the context of a virus remains insufficiently studied. Therefore, we introduced the JO4 mutation to various adenoviral vectors to explore their infection properties. In the current experimental settings and investigated cell lines, the JO4-containing vectors showed no enhanced transduction compared with their parental vectors in DSG2-high cell lines. Moreover, in DSG2-low cell lines, the JO4 vectors presented a rather weakened effect. Interestingly, DSG2-negative cell line MIA PaCa-2 even showed resistance to JO4 vector infection, possibly due to the negative effect of JO4 mutation on the usage of another Ad3 receptor: CD46. Together, our observations suggest that the JO4 vectors may have an advantage to prevent CD46-mediated sequestration, thereby achieving DSG2-specific transduction.